To subtract \(4.66 \times 10^{-5}\) and \(7.34 \times 10^{-7}\), we first need to express both numbers with the same exponent.
Convert \(4.66 \times 10^{-5}\) to have the same exponent as \(7.34 \times 10^{-7}\):
\[ 4.66 \times 10^{-5} = 4.66 \times 10^{-5} \times \frac{100}{100} = 4.66 \times 10^{-5} \times \frac{10^2}{10^2} = 4.66 \times 10^{-3} = 466 \times 10^{-5} \]
Now we have:
\[ 466 \times 10^{-7} - 7.34 \times 10^{-7} \]
Now, perform the subtraction:
\[ (466 - 7.34) \times 10^{-7} = 458.66 \times 10^{-7} \]
Now, we can express this in proper scientific notation:
\[ 458.66 \times 10^{-7} = 4.5866 \times 10^{-5} \]
So, the result of the subtraction is:
\[ \boxed{4.5866 \times 10^{-5}} \]